The Pantawid Pamilyang Pilipino Program Ten Years Hence: Lessons Learned and Ways Forward from a Decade of Implementing the Largest Conditional Cash Transfer Program in Southeast Asia - Basas, Rachel Mary Anne Arca (H. : ĐHKT, 2020)
Over the years, countries all over the world have achieved a marked increase in their economic growth rates as reflected in their respective GNPs and GDPs. The entry of the Millennium Development Goals in 2000 accelerated the achievement of various goals, most remarkably improvements in education and health outcomes in developing countries. However, despite this catalyst, the poor, vulnerable, and disadvantaged populations continue to benefit little from these progresses which do not seem to trickle down to the individual level. In addition, this sector of society is struggling to escape from the vicious and intergenerational cycle of poverty. This is where the government and its social protection systems come in. Social protection systems, according to the World Bank, help the poor and vulnerable “mitigate economic and fiscal shocks”i, and at the same time, gives them “a chance to climb out of poverty”.ii Given this context, which is also supported by various studies - social protection systems are the way out from intergenerational cycle of poverty through investments in human capital development.